Neural Representation of Auditory Size in the Human Voice and in Sounds from Other Resonant Sources - von Kriegstein, Katharina (Cell Press, 2007)
The size of a resonant source can be estimated by the acoustic-scale information in the sound [1–3]. Previous studies revealed that posterior superior temporal gyrus (STG) responds to acoustic scale in human speech when it is controlled for spectral-envelope change (unpublished data). Here we investigate whether the STG activity is specific to the processing of acoustic scale in human voice or whether it reflects a generic mechanism for the analysis of acoustic scale in resonant sources. In two functional magnetic resonance imaging (fMRI) experiments, we measured brain activity in response to changes in acoustic scale in different categories of resonant sound (human voice, animal call, and musical instrument). We show that STG is activated bilaterally for spectral-envelope changes in general; it responds to changes in category as well as acoustic scale. Activity in left posterior STG is specific to acoustic scale in human voices and not responsive to acoustic scale in other resonant sources. In contrast, the anterior temporal lobe and intraparietal sulcus are activated by changes in acoustic scale across categories. The results imply that the human voice requires special processing of acoustic scale, whereas the anterior temporal lobe and intraparietal sulcus process auditory size information independent of source category.